2010
DOI: 10.1002/fam.1066
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of polymer pyrolysis rate: Effect of property variations

Abstract: SUMMARYThe mass loss rate (MLR) of poly(methyl methacrylate) (PMMA) exposed to known radiant fluxes is simulated with two recently developed numerical codes, the National Institute of Standards and Technology (NIST) Fire Dynamics Simulator (FDS) and the Federal Aviation Administration (FAA) ThermaKin. The influence of various material properties (thickness, thermal conductivity, specific heat, absorption of infrared radiation, heat of reaction) on mass loss history is assessed, via their effect on the ignition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 27 publications
(45 reference statements)
3
41
0
1
Order By: Relevance
“…The ignition time is more strongly affected: lowering a from 6000 to 1000 m −1 increases the ignition time by a factor of 3 at 200 kW m −2 and 1.5 at 50 kW m −2 . Of course, the relative effects will differ if the polymer properties vary from those in reference . It is also noteworthy that the measured broadband absorption coefficient for black PMMA in the present work (as indicated in Figure ) is outside the range of values (333 to 2000 m −1 ) found in the literature by Bal and Rien , when a sample thickness is considered in which most of the energy is absorbed.…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…The ignition time is more strongly affected: lowering a from 6000 to 1000 m −1 increases the ignition time by a factor of 3 at 200 kW m −2 and 1.5 at 50 kW m −2 . Of course, the relative effects will differ if the polymer properties vary from those in reference . It is also noteworthy that the measured broadband absorption coefficient for black PMMA in the present work (as indicated in Figure ) is outside the range of values (333 to 2000 m −1 ) found in the literature by Bal and Rien , when a sample thickness is considered in which most of the energy is absorbed.…”
Section: Resultsmentioning
confidence: 45%
“…Given the IR absorption properties of the polymers described above, the influence of absorption coefficient on the burning behavior can be inferred. Using the simulated results in reference for the modeled thermoplastic, values of a between 1000 and 6000 m −1 will have a minor effect on the shape of the mass loss versus time curve. Likewise, this increase in a lowers the average burning rate by about 9% at an external heat flux of 21 kW m −2 and raises it by about 4% at 200 kW m −2 , whereas for (50, 100, or 150) kW m −2 , the effect is only a few percentage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that in-depth radiation is 4 the primary cause of delayed ignition time for PMMA samples, especially at higher heating rates, which also interpreted the deviation from linearity of the ignition data at high HF. Some other researchers performed sensitivity analyses, emphasizing the sensitivity coefficients of relevant model outputs with respect to the inputs, to study the importance of absorption mode [29][30][31]. Jiang [28] and Linteris [32] measured the average absorption coefficient of several polymers that can be inputted into numerical models, and also they provided generalized techniques for other polymeric materials.…”
Section: Introductionmentioning
confidence: 99%